Akibat Hukum Wanprestasi Dalam Jual Beli Tiket Konser Coldplay Secara Online - Andhryani Hasibuan, Saskia; Faisal, Faisal (UNES Law Review, 2024)
In this modern era, the interest of Indonesian society, especially the younger generation, in music concerts is increasing. Many consumers prefer to purchase tickets online due to its convenience, but frequent concert ticket cancellations leave them disappointed and at a loss. The normative research method is used to analyze the relevant laws, with Article 1320 of the Indonesian Civil Code serving as a guide for online buying and selling agreements. Breach of contract often occurs in online concert ticket sales, leading to legal consequences under Article 1243 of the Indonesian Civil Code. Buyers have the right to demand contract fulfillment and compensation for losses due to the seller's negligence.